On the photonic dispersion of periodic superlattices made of left-handed materials - Cavalcanti, Solange B.; Reyes-Gómez, Ernesto; Bruno-Alfonso, Alexys [UNESP]; Carvalho, Carlos A. A. De; Oliveira, Luiz E. (Springer Nature, 2010)
Studies of the band gap properties of one-dimensional superlattices with alternate layers of air and left-handed materials are carried out within the framework of Maxwell's equations. By left-handed material, we mean a material with dispersive negative electric and magnetic responses. Modeling them by Drude-type responses or by fabricated ones, we characterize the n(ω) = 0 gap, i.e., the zeroth order gap, which has been predicted and detected. The band structure and analytic equations for the band edges have been obtained in the long wavelength limit in case of periodic, Fibonacci, and Thue-Morse superlattices. Our studies reveal the nature of the width of the zeroth order band gap, whose edge equations are defined by null averages of the response functions. Oblique incidence is also investigated, yielding remarkable results. © 2010 Springer Science+Business Media B.V.
Keywords: Left-handed materials; One-dimensional stacks; Plasmon polaritons